2017
DOI: 10.1099/jgv.0.000914
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in intracellular transport of plant viral movement proteins BMB2 and TGB3

Abstract: The cell-to-cell transport of many plant viruses through plasmodesmata requires viral movement proteins (MPs) encoded by a 'triple gene block' (TGB) and termed TGB1, TGB2 and TGB3. TGB3 is a small integral membrane protein that contains subcellular targeting signals and directs both TGB2 and the helicase domain-containing TGB1 protein to plasmodesmata-associated structures. Recently, we described a 'binary movement block' (BMB) coding for two MPs, BMB1 and BMB2. The BMB2 protein associates with endoplasmic ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The constructs for the transient expression of BMB1, BMB2 and its N‐ and C‐terminal fusions to fluorescent proteins, ST‐GFP, ER‐GFP, ER‐monomeric red fluorescent protein (mRFP), PVX‐POL‐GFP (Lazareva et al ., 2017a,b), VAP27‐mRFP (Atabekova et al ., 2018), as well as constructs YN, YC, YN‐ER and YC‐ER used for membrane protein topology studies (Zamyatnin Jr. et al ., 2006), were described previously. To obtain binary vectors carrying PVX TGB2 and TGB3 genes, the respective fragments from constructs pRT‐12K and pRT‐8K (Solovyev et al ., 2000) were subcloned into pLH* (Solovyev et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The constructs for the transient expression of BMB1, BMB2 and its N‐ and C‐terminal fusions to fluorescent proteins, ST‐GFP, ER‐GFP, ER‐monomeric red fluorescent protein (mRFP), PVX‐POL‐GFP (Lazareva et al ., 2017a,b), VAP27‐mRFP (Atabekova et al ., 2018), as well as constructs YN, YC, YN‐ER and YC‐ER used for membrane protein topology studies (Zamyatnin Jr. et al ., 2006), were described previously. To obtain binary vectors carrying PVX TGB2 and TGB3 genes, the respective fragments from constructs pRT‐12K and pRT‐8K (Solovyev et al ., 2000) were subcloned into pLH* (Solovyev et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…thaliana Derlin1 (Der1) (Lee et al, 2013), an integral ER protein with four transmembrane segments and with its N-and Ctermini presumably located in the cytoplasm (Katiyar et al, 2005). Expression of Der1 fused to GFP at its C-terminus (Der1-GFP) together with luminal ER-mRFP marker (Lazareva et al, 2017a) led to overlapping patterns of red and green fluorescence, highlighting the normal structure of the cortical ER network ( Fig. 2a-c) in agreement with the previously described localization of A. thaliana Derlin1 to the ER membranes (Katiyar et al, 2005).…”
Section: New Phytologistmentioning
confidence: 99%
See 1 more Smart Citation
“…BMB-like gene modules consisting of two genes were also identified in plant transcriptome RNA-seq data assembled into RNA virus-like contigs [virus-like RNA assemblies (VLRA)] ( Morozov and Solovyev, 2015 ). HGSV BMB1 and BMB2 were found to be necessary and sufficient to mediate viral cell-to-cell movement ( Lazareva et al, 2017b ), and further studies revealed similarities in mechanisms of intracellular transport of BMB and TGB proteins ( Lazareva et al, 2017a ). Taking into account a distant relationship of TGB and BMB proteins, we hypothesize that the BMB transport module could represent an evolutionary snapshot of intermediate stage of TGB evolution corresponding to the TGB1/TGB2 genomic block.…”
Section: Origin and Functional Significance Of Small Membrane Proteinmentioning
confidence: 99%
“…Moreover, BMB2 directs BMB1, having helicase activity, to the membrane bodies, to the Pd interior cavity and to neighboring cells [58] . The BMB2 intracellular transport to Pd-associated sites does not involve the secretory pathway, but requires the functional ER/actin network [168] .…”
Section: Binary Movement Blockmentioning
confidence: 99%